De moças (1926 -1960 1960) a ex-moças (1983 1987): representações e práticas de leitura instituídas na Coleção Biblioteca das Moças - Lang, Cintia da Silva (2008)
The present work intends to treat about two questions: the study of the assembly and organization phases of the Biblioteca das Moças collection and the study of the absorption concerning the formation, culture and identity of the readers of this sort of literature. The objectives of this research lead us to analyze from different primary sources, as the editorial movement files, with the intention to get informations about the kinetics of the book s production, allowing to verify how was the first editorial project and all the changes that it suffered along the years of the collection s life. The information collected allow to confirm that the life time of the Biblioteca das Moças collection were between 1926 and 1960, with a last edition of a few books between 1982 and 1987. Analyzing the production s dynamics we could observe three different periods of the collection s production, influenced by the social and reader s changes, and also by the dynamics of the internal production. Studying the letters sent by the readers of the Biblioteca das Moças collection in the 80 s, we found indications of appropriations of behavior rules hidden in this books, and also the characterization that the publishing company made of the consumers, with the intention of select the right type of books to the readers, fact that would guarantee the commercial success of the Biblioteca das Moças collection for a long period